Acid-Base, Electrolyte and Lactate Abnormalities as Well as Gastric Necrosis and Survival in Dogs With Gastric Dilation-Volvulus Syndrome. A Retrospective Study in 75 Dogs - Rauserova-Lexmaulova, Leona; Vanova-Uhrikova, Ivana; Rehakova, Kristina (Topics in companion animal medicine, 2020)
Gastric dilation-volvulus (GDV) syndrome in dogs is associated with complex metabolic, acid-base, and electrolyte abnormalities. The aim of this study was to evaluate previously analyzed factors (lactate and BE) in combination with other acid-base parameters (pH, pCO2, bicarbonate, base excess [BE], anion gap [AG], and strong ion difference) and electrolyte concentrations and to evaluate their association with the incidence of gastric necrosis and outcome in dogs with GDV. A retrospective study in 75 dogs with gastric dilation-volvulus syndrome, University veterinary teaching hospital. Medical records were reviewed including signalment, history, initial plasma lactate, acid-base parameters, and electrolyte concentrations, surgical findings and outcome. The overall mortality was 18.7%. In dogs with gastric necrosis, higher initial plasma lactate (median 5.84 vs. 3.36 mmol/L) and AG (20.7 vs. 16.55 mmol/L) and lower pH (7.29 vs. 7.36), bicarbonate (18.7 vs. 22.9 mmol/L), and BE concentration (-8.1 vs. -1.85 mmol/L) were found compared to dogs without gastric necrosis. Anorganic phosphorus was the only electrolyte investigated for which a significant difference was noted between dogs with and without gastric necrosis (1.93 vs. 1.39 mmol/L). The initial plasma lactate concentration (3.36 mmol/L vs. 9.68 mmol/L) and AG (16.8 vs. 20.95 mmol/L) were lower in survivors than nonsurvivors. Survivors had higher pH (7.35 vs. 7.27), bicarbonate concentrations (22.9 vs. 17.35 mmol/L), and BE (-1.9 vs. -9.55 mmol/L) compared to nonsurvivors. Anorganic phosphorus was ultimately the only electrolyte with a significant difference between survivors and nonsurvivors (1.4 vs. 1.84 mmol/L). A multivariate logistic regression model of combination lactate, pH, bicarbonate, BE, AG, and anorganic phosphorus identified pH ≤7.331 and bicarbonate as factors independently associated with gastric necrosis. Similarly, pH ˃7.331, bicarbonate and anorganic phosphorus were independently associated with outcome. Higher initial plasma lactate, AG and anorganic phosphorus levels, and lower pH, BE and bicarbonate concentrations were found in GDV dogs with gastric necrosis. Similarly, initially higher plasma lactate, AG and anorganic phosphorus concentrations, and lower pH, BE and bicarbonate were found in GDV dogs who required euthanasia or who died after surgery. Of these parameters, pH and bicarbonate were strongly and independently associated with gastric necrosis, and pH, bicarbonate and phosphorus were independently associated with outcome.
Keywords: analýza přežití; dilatace žaludku; psi; Retrospective Studies; Survival Analysis; kyselina mléčná; koncentrace vodíkových iontů; Česká republika; acid-Base; Dogs; Records; Lactic Acid; mužské pohlaví; Necrosis; Gastric Dilatation; Dog Diseases; disorders; Czech Republic; Stomach; žaludek; nemoci psů; ženské pohlaví; zvířata; retrospektivní studie; Hydrogen-Ion Concentration; Stomach Volvulus; gastric-dilation volvulus; outcome; electrolytes; elektrolyty; nekróza; Electrolytes; syndrom; záznamy jako téma; Female; volvulus žaludku; Syndrome; Male; Animals